2022
DOI: 10.1038/s41598-022-16874-0
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging plant physiological dynamics using physical reservoir computing

Abstract: Plants are complex organisms subject to variable environmental conditions, which influence their physiology and phenotype dynamically. We propose to interpret plants as reservoirs in physical reservoir computing. The physical reservoir computing paradigm originates from computer science; instead of relying on Boolean circuits to perform computations, any substrate that exhibits complex non-linear and temporal dynamics can serve as a computing element. Here, we present the first application of physical reservoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…[ 59 ] Such components can be used to communicate and better leverage the intrinsic computational capabilities of plant's physiological dynamics. [ 60 ] For example, in a hydra model, the ETE‐S was polymerizing during the foot regeneration at the amputation site forming a conducting layer simultaneously with the newly forming tissue. Although these devices required addressing with external electrodes and did not have a record performance, they open the pathway for a new paradigm on how technological components are integrated in living tissues.…”
Section: Evolvable Self‐organized and Random Networkmentioning
confidence: 99%
“…[ 59 ] Such components can be used to communicate and better leverage the intrinsic computational capabilities of plant's physiological dynamics. [ 60 ] For example, in a hydra model, the ETE‐S was polymerizing during the foot regeneration at the amputation site forming a conducting layer simultaneously with the newly forming tissue. Although these devices required addressing with external electrodes and did not have a record performance, they open the pathway for a new paradigm on how technological components are integrated in living tissues.…”
Section: Evolvable Self‐organized and Random Networkmentioning
confidence: 99%
“…In plants, the tissue integrated OMIECs in combination with the natural electrolytic environment were used to demonstrate the possibility of utilizing the in-vivo organized OMIECs in devices [56]. Such components can be used to communicate and better leverage the intrinsic computational capabilities of plant's physiological dynamics [57]. For example, in a hydra model, the ETE-S was polymerizing during the foot regeneration at the amputation site forming a conducting layer simultaneously with the newly forming tissue.…”
Section: Collective Behavior: Beyond Digitalmentioning
confidence: 99%
“…Nakajima et al [ 11 , 12 ] have shown that such a soft robotic arm has a short-term memory and can be used to solve several computational tasks in real time. In addition, a recent study has shown that even biological entities such as plants may be used as a physical reservoir [ 13 ].…”
Section: Introductionmentioning
confidence: 99%